Study of the S427G polymorphism and of MYBL2 variants in patients with acute myeloid leukemia. Issue 2 (1st February 2016) - Dolz, Sandra; García, Paloma; Llop, Marta; Fuster, Óscar; Luna, Irene; Ibáñez, Mariam; Gómez, Inés; López, María; Such, Esperanza; Cervera, José; Sanz, Miguel A.; De Juan, Inmaculada; et al.
Abstract : Dysregulation of MYBL2 has been associated to tumorigenesis and the S427G polymorphism could induce partial inactivation of MYBL2, associating it with cancer risk. It has previously been shown that MYBL2 was over-expressed in some acute myeloid leukemias (AML), portending poor prognosis. However, to date no studies have investigated the S427G or other genetic variants of MYBL2 in AML. This study analyzed the S427G in 197 AML patients and 179 controls and screened the MYBL2 sequence in patients. In contrast to other studies in solid tumors, the S427G was not associated with the incidence of AML. This study detected four unannotated genetic alterations, of which the Q67X could be involved in MYBL2 dysfunction. Eight polymorphisms were identified, among which the rs73116571, located in a splicing region, was associated with higher incidence in AML and weaker MYBL2 expression, suggesting pre-disposition to AML. Additional functional studies should be performed to verify these genetic variations as possible targets in AML.